«Tῆς αὐτοχείρου γραφῆς». Scrittura e libri nell’epistolario di Teodoro Studita - Sietis, Nina (Scrineum, 2021)
The epistolary collection of Theodore the Studite (759-826), although incomplete, counts more than 500 letters, which prove to be a fundamental resource for reconstructing the life and activity of the famous iconodule. Surprisingly enough, the letters have never been considered for investigating the graphic activity of Theodore and the monks of the Constantinopolitan coenobium of Studios. The present contribution tries to remedy this lack, proposing some reflections on the compositional practices typical of the Studite abbot and his addressees, on the ways in which they exchanged letters and their literary works, on the material aspects of writing and on the books they read.